Case report: Transfusion independence and abolition of extravascular hemolysis in a PNH patient treated with pegcetacoplan - Fattizzo, Bruno; Versino, Francesco; Zaninoni, Anna; Marcello, Anna Paola Maria Luisa; Vercellati, Cristina; Artuso, Silvia; Barcellini, Wilma (Frontiers in Immunology, 2022)
More than half of patients with paroxysmal nocturnal hemoglobinuria (PNH) treated with complement fraction C5 inhibitors experience residual anemia and hemolysis. This is partly due to the persistent activation of the complement cascade upstream C5, resulting in C3 deposition on PNH erythrocytes and extravascular hemolysis in the reticuloendothelial system. Pegcetacoplan is the first proximal C3 inhibitor to be approved in PNH basing on favorable efficacy and safety data in both naïve and eculizumab treated PNH. Here we report the first Italian patient treated with pegcetacoplan in a named patient program. The patient suffered from hemolytic PNH associated with CALR+ myeloproliferative neoplasm and was heavily transfusion dependent despite eculizumab therapy. Treatment with pegcetacoplan induced a dramatic improvement in Hb, along with normalization of unconjugated bilirubin and reticulocytes, as markers of extravascular hemolysis. Sequential laboratory workup showed the disappearance of C3 deposition on erythrocytes by direct anti-globulin test, the increase of PNH clone on erythrocytes, and a peculiar right shift of the ektacytometry curve. The drug was well tolerated, and the patient reported a significant improvement in his quality of life. Overall, pegcetacoplan appears a safe and effective option “ready to use” in the clinic for patients with PNH and suboptimal response to anti-C5 agents.